CFD analysis of flow field in aromatics extraction unit. Issue 1 (June 2020) - Zhou, Chenglong; Chen, Tao; Chen, Tao; Li, Zhipeng; Li, Xingfeng
Abstract: The technology of monitoring and tracing the unorganized emissions of VOCs in petrochemical parks is a research hotspot. The characteristics of the wind field at the monitoring point are the key to traceability. Aiming at the Daqing Refinery aromatics extraction equipment, the CFD method was used to simulate the transient flow in the equipment area under 160 ° and 300 ° atmospheric wind. The results show that the flow direction of the local flow field at different positions is different, and the stability of the flow direction is also inconsistent. The local flow field at the monitoring point is related to both the location and the wind direction. When the natural wind changes, the direction and stability of the flow field also change. The flow stability in the vortex region is poor.